PENGKOMBINASIAN LOGAM DAN KAYU PADA SENI KRIYA KARYA I KETUT SADIA - Wayan Sudiarta; I Nyoman Sila; Putu Krisna Yuda Utama (Universitas Pendidikan Ganesha, 2023)
This research aims to examine the production process, product forms, as well as supporting and inhibiting factors in developing metal-wood combination crafts at Ketut Sadia Craftsmen in Sari Mekar Village, Buleleng Regency. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research results show that the metal-wood combination crafts produced by Ketut Sadia consist of plaques or trophies and command sticks. These works are a combination of metal and wood, adorned with Bali's distinctive metal carvings and predetermined symbols. The process of creating metal works involves the use of various tools such as chisels, calipers, hammers, and metal cutting tools. Copper is the commonly used metal material, while teak wood is chosen for its fiber and strength. Ketut Sadia has successfully created various unique crafts by combining metal and wood. This research also discusses the principles of metal-wood combination techniques in craft art. Metal craft utilizes various processing techniques tailored to the type of metal material used. The use of materials such as aluminum, silver, and brass requires different processing methods. Additionally, Ketut Sadia also combines metal with teak wood, which has good fiber characteristics, strength, and durability. This research provides a deep understanding of the various forms of metal-wood combination crafts, the principles of combination techniques, and aesthetic assessment in the craft art produced by Ketut Sadia. The findings of this research can serve as a reference and inspiration for other craftsmen in developing metal-wood combination crafts with a unique and distinctive approach.